Optimization of Energy Management Strategy for Plug-in Axle-split Hybrid Electric Vehicle - Du Changqing; He Biao; Cao Xiliang; Wang Huawu; Ren Weiqun (Jixie chuandong)
In order to improve the energy consumption economy of a plug-in axle-split hybrid electric vehicle （PHEV），a rule-based energy management strategy is established，and the corrected power factor and speed limits value for engine startup are introduced. The key parameters of the corrected power factor of engine，start-up speed and energy management strategy control rules are optimized offline by using particle swarm optimization （PSO）. On the AMESim-Simulink co-simulaton platform，the optimization model is established and simulated. The results indicate that compared with the non-optimized energy management strategy，the energy consumption economy of the optimized control strategy has been significantly improved，and the overall energy consumption of the vehicle has been reduced by 12.6%.